Processo de escolha de bancos de imagens: aplicações no marketing business to business - Borges, Camila de Moraes Barbosa (2007)
The general objective of this research is to verify which attributes are most relevant to a stock photography agency that represent the purchaser's standards of choice. For this objective to be accomplished, qualitative interviews with the customers of stock photography agencies had been made in order to raise the attributes considered with relevance in the process of choice for the Brazilian stock photography agency market. The levels of each attribute to be tested had arisen through the mapping of the products and services offered by the competition and the relative weight assigned to each one of the attributes related to the research in the choices for a stock photography agency. A transversal study was made with a sample of stock photography agencies customers from Brazil¿s Southeastern region. For the analysis of this data, a survey method was used, that, according to MALHOTRA (2006: 182), involves a structuralized questionnaire to be answered by an interview that elucidates specific information, in which the questions had a predetermined order. This questionnaire was presented through interviews on the Internet. The method adopted for this analysis was a joint analysis. A sampling of 1000 customer stock photography agencies were selected, which were represented by a didactic book editor, advertising agencies, editorial companies, etc., in the states of Rio de Janeiro, São Paulo, Espírito Santo and Minas Gerais. They had been obtained by 16 stimulations, or cards, for the application of the companies. Of the sample of 1000 customers of stock photography agencies, 7,8% responded to the research. The attribute most relevant in accordance with the presented results is the availability of images in high resolution for layout. Its relative importance was 40,78%. At the end of the study, the management implications were propitiated to the stock photography agencies managers inabling them to be more competitive.